Caring about Preemies' Safe Sleep (CaPSS): An Educational Program to Improve Adherence to Safe Sleep Recommendations by Mothers of Preterm Infants. Issue 4 (October 2018) - Dowling, Donna A.; Barsman, Sarah Gutin; Forsythe, Paula; Damato, Elizabeth G.
Abstract : Preterm infants born before 37 weeks' gestation die of sudden infant death syndrome (SIDS) at a rate more than double that of term infants. There is a need for SIDS prevention programs tailored to the specific needs of parents of high-risk infants. The purpose of this study was to pilot test an online educational module addressing SIDS risk-reduction recommendations (RRRs) for parents of preterm infants. This study was conducted in a 44-bed transitional care unit at a level IV NICU in the Midwest. A repeated-measures design was used. Two weeks before discharge, mothers completed a survey, addressing knowledge and plans for caring for their baby at home. Mothers then viewed the 5-section Caring about Preemies' Safe Sleep (CaPSS) education module and completed the postmodule evaluation. A discharge survey was completed 4 weeks postdischarge. Fifteen mothers, mean age 26.4 years, participated; 8 (53%) returned the postdischarge survey. Module evaluation rated clarity and completeness of information high. Mothers' ratings of SIDS knowledge were significantly higher after viewing the module ( P = .000) and 4 weeks after discharge home ( P = .012). Mothers found the use of a pacifier at sleep times to be new information and changed their plans for caring for their infant, with 28.6% of mothers always offering a pacifier before sleep after discharge compared with the 6.7% who had planned to do this before discharge. However, only 71% of infants slept in parents' room after discharge and only 41% were receiving at least some breast milk, which are not consistent with SIDS RRRs.